Long-term safety of tiotropium delivered by Respimat® SoftMist™ Inhaler: patient selection and special considerations - Tan CK; Say GQ; Geake JB (Dove Medical Press, 2016)
Ching Kuo Tan, Gui Quan Say, James B Geake Department of Respiratory Medicine, Lyell McEwin Hospital, Elizabeth Vale, SA, Australia Abstract: Tiotropium bromide is a long-acting inhaled muscarinic antagonist used in patients with chronic respiratory disease. It has been available since 2002 as a single-dose dry powder formulation via the HandiHaler® dry powder inhaler (DPI) device, and since 2007 as the Respimat® SoftMist™ Inhaler (SMI). The latter is a novel method of medication delivery that utilizes a multidose aqueous solution to deliver the drug as a fine mist. Potential benefits include more efficient drug deposition throughout the respiratory tract, reduced systemic exposure, and greater ease of use and patient satisfaction compared with the use of HandiHaler DPI. Although tiotropium bromide delivered via the HandiHaler DPI has been clearly shown to improve lung function, dyspnea, and quality of life and to reduce exacerbations in patients with chronic obstructive pulmonary disease (COPD), there is accumulating evidence regarding the use of tiotropium HandiHaler in other respiratory diseases characterized by airflow limitation, such as asthma and cystic fibrosis. Developed more recently, tiotropium delivered via the Respimat SMI appears to have a similar efficacy and safety profile to the HandiHaler DPI, and early data raising the possibility of safety concerns with its use in COPD have been refuted by more recent evidence. The benefits over the HandiHaler DPI, however, remain unclear. This paper will review the evidence for tiotropium delivered via the Respimat SMI inhaler, in particular as an alternative to the HandiHaler DPI, and will focus on the safety profile for each of the chronic lung diseases in which it has been trialed, as well as an approach to appropriate patient selection. Keywords: tiotropium, Respimat, safety, COPD, asthma, HandiHaler